Efecto del consumo de dieta líquida y alimento balanceado sobre el crecimiento y desarrollo ruminal en terneras de lechería - Elizondo-Salazar, Jorge Alberto (2013)
Effect of liquid and solid diet intakeon growth and rumen development of dairycalves. The objective of this study was todetermine the effect of liquid and solid dietintake on growth and rumen development ofdairy calves. The experiment was conducted in acommercial dairy farm located at 2500 m.a.s.l inthe province of Cartago, Costa Rica. Ten Holsteincalves were selected at birth and randomlyincluded in 1 of 2 treatments. The conventionaltreatment consisted in providing calves a liquiddiet on a restricted basis (4 l.calf-1.d-1). Theintensive treatment consisted in supplying calvesthe same liquid diet in larger quantities, up to8 l.calf-1.d-1. Growth measurements includingbody weight, hip height and withers height weretaken weekly. Calves were sacrificed at 8 weeksof age, in order to compare rumen growth anddevelopment. Animals in the intensive treatmenthad a significantly higher liquid diet intake andlower feed intake than calves in the conventionaltreatment. Growth measurements showed nosignificant differences between treatment groups.Calves in the intensive treatment had a poorrumen development and lesser papillae growth, which may negatively affect calves’ post-weaning performance.